2021
DOI: 10.1111/clr.13820
|View full text |Cite
|
Sign up to set email alerts
|

The use of rhBMP2 for augmentation of established horizontal/vertical defects may require additional use of rhVEGF to achieve significant bone regeneration: An in vivo experimental study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This indicates an early hampering effect of the scaffolds themselves on bone regeneration. Kauffmann and coworkers observed a similar effect for particles made of PDLLA/CaCO 3 that were implanted into 3-monthold, not already healed bone defects in the alveolar crest of the maxillae of minipigs [39]. After 4 weeks of healing, PDLLA/CaCO 3 -treated animals showed less newly formed bone compared to SHAM-operated animals, with no signs of the induction of bone formation between the PDLLA/CaCO 3 particles that were furthermore separated from the underlying native bone by a fibrous tissue layer.…”
Section: Discussionmentioning
confidence: 72%
“…This indicates an early hampering effect of the scaffolds themselves on bone regeneration. Kauffmann and coworkers observed a similar effect for particles made of PDLLA/CaCO 3 that were implanted into 3-monthold, not already healed bone defects in the alveolar crest of the maxillae of minipigs [39]. After 4 weeks of healing, PDLLA/CaCO 3 -treated animals showed less newly formed bone compared to SHAM-operated animals, with no signs of the induction of bone formation between the PDLLA/CaCO 3 particles that were furthermore separated from the underlying native bone by a fibrous tissue layer.…”
Section: Discussionmentioning
confidence: 72%
“…Six studies reported chronic type BD in the mandibular ( n = 5; 2–4.5 cm long buccal defects) (Duong et al., 2023; Herford et al., 2012; Stricker et al., 2014; Yeo et al., 2012; Zambon et al., 2012) or maxillary alveolar ridge ( n = 1; 2 cm long buccal defect) (Kauffmann et al., 2021). In all studies, tooth extraction and BD were performed in a preliminary surgery followed by a healing period (4–12 weeks) to allow ‘chronification’ (mimicking atrophic ridges) before application of the regenerative procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows several cytokines loaded with bone biomaterials that promote angiogenesis and osteogenesis. Among all these factors, VEGF is the most commonly used in bone tissue engineering (Li et al, 2020b;Kauffmann et al, 2021).…”
Section: The Effect Of Cytokine-loaded Bone Bioscaffolds On Angiogenesismentioning
confidence: 99%